Effect of Age on the Biochemical and Hematological Blood Profile in the Arabian Horses Raised in Libya - Fathia Benashour; Mansur Shmela; Salheen Salheen; Fahima Alnagar; Rabea Al-Zlitni (AlQalam Journal of Medical and Applied Sciences, 2024)
Normal hematological and biochemical values need to be defined for each equine age in order to increase diagnostic precision. The present study was aimed to monitor the hematobiochemical characteristics of 65 clinically healthy Arabian horses raised in Libya with an age of less than or equal 3 years (young) or more than 3 years (stallion). The results showed that MCHC were significantly (p<0.0001) higher in the young horses than stallions, while the reverse for HCT, MCV, RDW-CV, RDW-SD, and MPV. On the other hand, Hb, RBC, MCH, PDW and PCT showed non-significant change with the variations between Arabian horse’s ages. The total leukocyte and platelet counts were statistically increased in young horses but did not significantly different. Regarding activities of different enzymes (ALT, AST, ALP and LDH activity), there are significantly (p<0.05) increased values in young horses compared with stallions. However, the serum TP, TB and DB were significantly (p<0.005) higher in adult horses than young one. There are significant and non-significant differences in some lipid profile and electrolytes between animals according to age factor. In abbreviate, results of this study showed that both blood and biochemical parameters clearly alterated under the effect of age in this breed of horses. إن من أهم ميزات تحديد القيم الدموية والكيميائية الحيوية الطبيعية لمختلف أعمارالخيول زيادة دقة التشخيص عند تعرضها لأي عارض مرضي أو فسيولوجي عابرحتى يتم تجنب أي خسائربسسب المرض من جهة والتخلص من عوامل الوهن والضعف التي قد تأثر على العائد العام لهذا الفصيل من مملكة الحيوان المستأنس. من هذا المنطلق هدفت الدراسة الحالية إلى مراقبة الخصائص الدموية والكيميائية لـ 65 من الخيول العربية السليمة سريريًا والتي تم تربيتها في ليبيا بعمر أقل أو يساوي 3 سنوات (صغير) أو أكثر من 3 سنوات (فحل). حيث أظهرت النتائج أن MCHC كانت أعلى معنويا (p<0.0001) في الخيول الصغيرة مقارنة بالفحول، بينما كان العكس في كل من HCT، MCV، RDW-CV، RDW-SD، وMPV. من ناحية أخرى، أظهرت نسبة Hb وRBC وMCH وPDW وPCT تغيراً غير معنوي إحصائيا تحت تأثيرإختلاف العمرفي الخيل العربية. عموما كانت هناك زيادة في إجمالي عدد كريات الدم البيضاء والصفائح الدموية إحصائيا في الخيول الصغيرة ولكن الإختلاف لم يكن كبيرا. فيما يتعلق بنشاط الإنزيمات المختلفة (نشاط ALT، AST، ALP و LDH)، هناك زيادة معنوية (p<0.05) في القيم في الخيول الصغيرة مقارنة بالفحول. مع ذلك، كانت مستويات TP و TB و DB أعلى معنويا (p<0.005) في الخيول البالغة مقارنة بالخيول الصغيرة. توجد فروق معنوية وغير معنوية في بعض مستويات الدهون والكهارل بين الحيوانات تبعاً لعامل العمر. نستطيع القول من خلال ما تحصلنا عليه من نتائج في هذه الدراسة أن كلا من مؤشرات الدم والكيمياء الحيوية تتغير بشكل واضح تحت تأثير عامل العمر في سلالة الخيول العربية التي نشأت في ليبيا